The relationship between accreditation standards and organizational excellence and their role in the excellence of administrative leadership - Alsaleem, Norah Abdulaziz Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2025)
This paper was conducted to determine the extent to which the King Abdulaziz Quality Award model can be applied in Saudi hospitals for excellence in performance in health services by analyzing, matching, and reaching a relationship between the requirements of the King Abdulaziz Quality Award excellence model standards and the leadership standards in the CBAHI National Accreditation Program. The researcher used Descriptive analytical approach and used the questionnaire and the National Accreditation Program as tools for the study. The research results showed that the criteria of the King Abdulaziz Quality Award model were 32% for leadership, 23% for operations, products, and services management, 20% for human resources, 12% for the strategic plan, 11% for partnerships and resources, and 15% for customer results, human resources results, and key performance results with the requirements of the leadership standard in the CBAHI Accreditation Program. These percentages indicate support and compatibility between excellence and accreditation programs with the relationship and convergence with each other. This result confirms that the existence of the CBAHI National Accreditation Program helps and supports administrative leaders to implement the King Abdulaziz Quality Award excellence model, which leads to excellence in performance in health services in Saudi government hospitals.
Keywords: King Abdul-Aziz Quality Award (KAQA); Saudi Central Board for Accreditation of Healthcare Institutions (CBAHI); Government hospitals; Performance excellence; Healthcare services